Entre éducation relative à l'environnement et éducation scientifique, quelles complémentarités ? - Anne Versailles (VertigO)
For some years now Europe has been faced with a crisis in the science sector characterized by young people's lack of interest for science, scientific studies or scientific careers. Many efforts are being made to try and turn the tables, but such initiatives are often structured around objectives that offer few prospects beyond the promotion of science itself. In this respect, environment-related education can serve as a leverage point in such a way as to place these initiatives in a project that is more citizen-oriented. Scientific education can thus provide such a project with the necessary breakthroughs so as to ask the necessary development questions thanks to the proper tools at one's disposal. At a later stage, environmental education provides a new relay for efforts within an extended social network, making it possible to confront and therefore expand knowledge, skills and behaviour.